Case Report: Dual-Energy Computed Tomography of Cardiac Changes in IgG4-Related Disease - Wang, Ying; Zhou, Hui; Hu, Ping; Zhao, Jie; Mao, Yitao; Li, Zhixiao; Zhao, Xi (Frontiers in Cardiovascular Medicine, 2022)
Background: Dual energy computed tomography (DECT) is used in coronary plaque characterization, myocardial perfusion imaging and pulmonary embolism diagnosis; however, there is no relevant research regarding DECT in IgG4-related diseases (IgG4-RD) involving the coronary artery. We are the ﬁrst to report of DECT findings about cardiac morphology and function in IgG4-RD. Patient Findings: Multimodality cardiovascular imaging from a 63-year-old male patient who presented with IgG4-related pancreatitis was analyzed. An iodine map and spectral curves were obtained from the DECT, which can help to distinguish between non-calcified plaques and IgG4 lesions of the coronary artery, non-invasive FFRCT (fractional flow reserve derived from coronary computed tomography angiography) and ECV (extracellular volume fraction) demonstrated myocardial ischemia and myocardial fibrosis respectively. Conclusions: DECT can detect coronary artery tumor-like lesions caused by IgG4-RD, and simultaneously assess the morphological, functional, and histological characteristics of the myocardium. This may help to guide individualized and timely treatment and avoid potentially life-threatening complications.